Influence of Silicate and Calcium Ions to Transport of Phosphate Ion through Polymeric Inclusion Membrane (PIM) - Barlah Rumhayati; Qonitah Fardiyah; Himayatul Musyarofi (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2017)
Measurement of phosphate ions by molybdenum blue method is influenced by the presence of interfering ions, such as silicate and calcium ions. To obtain an accurate measurement, interference ions should be separated from the phosphate ion. Separation could be carried out with extractions using PIM method. The effectiveness of separation based on PIM method depends to the transport efficiency of targeted ion from feed phase to stripping phase. The aim of this research was to determine the effect of silicate and calcium ions to phosphate ion transport through PIM. PIM was prepared by mixing PVC as polymer, 1,10-dekanadiol as a plasticizer, and Aliquat 336-Cl as extractant in the solvent THF. Extraction was performed by using a diffusion cell, The cell was consisted by two containers, i.e feed phase container and stripping phase container which was separated by PIM. Feed phase was a mixture of phosphate 100 mg / L and SiO32- at 5; 10; 15; 20 and 25 mg/L for studying the effect of silicate ion. Investigation of calcium ion effect was conducted by using a mixture of phosphate solution of 100 mg / L and Ca2+ of 1.13x10-4; 2.26x10-4 and 4.52x10-4 mg/L in the feed phase. The stripping phase was the solution of NaCl 0.1 M. Both containers were stirred for 3 hours at 180 rpm. The solution in the both containers was taken for 1 mL every 30 minutes. Phosphate ion was measured by visible spectrophotometry at 690 nm with molybdenum blue method. Silicate ion was determined by visible spectrophotometry at a wavelength of 410 nm with molybdenum blue method. Calcium ion was determined by AAS. The results showed that the higher concentration of calcium ions, the lower the phosphate ion transport efficiency. Only 34.46% of phosphate ions transported in the presence of calcium ions up to 4,52x10-4 mg/L. Meanwhile, PIM was more selective to silicate ion than ion phosphate at the silicate ion concentration up to 15 mg/L. At higher concentration of silicate ions, PIM was more selective to phosphate ion.